Nonlinear diffusion of gluons - Wolschin, Georg (Physica. A, Statistical mechanics and its applications, 2022)
It is proposed to consider the fast thermalization of gluons in relativistic heavy-ion collisions as a diffusion process in momentum space. Closed-form analytical solutions of a nonlinear boson diffusion equation (NBDE) with constant drift and diffusion coefficients v, D and boundary conditions at the singularity are derived. The time evolution towards local central temperatures T≲600 MeV through inelastic gluon scatterings in heavy-ion collisions is calculated for under- and overoccupied systems in the full momentum range. The results are consistent with QCD-based numerical calculations for gluon thermalization via inelastic gluon collisions.